A woman's rightful place? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
One of ORSTOM's female research scientists recently wrote: 'It is counterproductive to see development as something purely male and such an attitude gets now here. 'This view is shared by more and more development workers. African women carry heavy...